Determinants of Bank Closures: Exploring the Relationship between Neighborhood Characteristics and Bank Branch Locations. (2nd October 2022) - Aversa, Joseph; Shaker, Richard; Cleave, Evan; Salooja, Navdeep
Abstract: Retail Banking in Canada has experienced significant changes perpetuated by both digital trends in retail and changes in consumer demand. These changes have resulted in significant decreases in client interactions with physical branches in favor of digital platforms (online, mobile, phone banking). As the "Big Five" Canadian banks pursue network optimization strategies focused on reinvesting savings into their digital channels, branch closures will accelerate, resulting in market gaps. Thus, the central aim of this study is to understand the relationship between neighborhood characteristics (built environment and socio-economic) and bank branch locations. Using the city of Toronto as a case study, this research addresses three objectives: (i) to identify neighborhoods underserviced by the "Big Five" Canadian banks; (ii) to examine the spatial relationship between neighborhood characteristics and branch locations; and (iii) to quantify the key neighborhood characteristics linked to branch locations. This study finds that financial exclusion continues to be associated with local dynamics of physical topography, road network, demographics, and socio-economic status. While financial exclusion is becoming a growing area of concern for policy makers, this research finds that access to affordable financial services still proves to be an issue that requires attention.